Effects of Transcranial Direct Current Stimulation of Primary Motor Cortex on Reaction Time and Tapping Performance: A Comparison Between Athletes and Non-athletes - Seidel, Oliver; Ragert, Patrick (Frontiers in Human Neuroscience, 2019)
Recent studies provided compelling evidence that physical activity leads to specific changes on a functional and structural level of brain organization. The observed neural adaptions are specific to the sport and manifested in those brain regions which are associated with neuronal processing of sport-specific skills. Techniques of non-invasive brain stimulation have been shown to induce neuroplastic changes and thereby also facilitate task performance. In the present study, we investigated the influence of transcranial direct current stimulation (tDCS) over the leg area of the primary motor cortex (M1) on simple reaction time tasks (RTT) and tapping tasks (TT) as a comparison between trained football (FB) and handball players (HB) and non-athletes (NA). We hypothesized that anodal tDCS over M1 (leg area) would lead to specific behavioral gains in RTT and TT performance of the lower extremity as compared to sham condition. On an exploratory level, we aimed at revealing if trained athletes would show stronger tDCS-induced behavioral gains as compared to NA, and, furthermore, if there are any differential effects between FB and HB. A total number of 46 participants were enrolled in a sham-controlled, double-blinded, cross-over study. A test block consisting of RTT and TT was performed before, during, after as well as 30 min after a 20-min tDCS application. Additionally, the specificity of tDCS-induced changes was examined by testing upper extremity using the same experimental design as a control condition. Our data showed no group- or sport-specific tDCS-induced effects (online and offline) on RTT and TT neither for lower nor upper extremities. These findings indicate that neither athletes nor NA seem to benefit from a brief period of tDCS application in speed-related motor tasks. However, more knowledge on neuronal processing of RTT and TT performance in trained athletes, the influence of tDCS parameters including stimulation sites, and the effect of inter-individual differences is required in order to draw a comprehensive picture of whether tDCS can help to enhance motor abilities on a high performance level.